Prenatal diagnosis of obstructed supracardiac total anomalous pulmonary venous connection at 23 weeks with successful immediate postnatal surgical correction - Danish Memon; Balu Vaidyanathan (Wolters Kluwer Medknow Publications, 2021)
Diagnosis of isolated total anomalous pulmonary venous connections (TAPVCs) is relatively rare in fetal life, especially in early gestation. We report a case of a fetus diagnosed with the supracardiac type of TAPVC at 23 weeks gestation, with evidence of obstruction to connection of the common vertical vein to the superior vena cava. The neonate had a critical presentation at birth and underwent an emergency surgical repair immediately after birth with excellent outcome on short term follow-up with the resolution of pulmonary artery hypertension.